Assessing main process mechanism and rates of sulfate reduction by granular biomass fed with glycerol under sulfidogenic conditions. (January 2022) - Zhou, X.; Fernández-Palacios, E.; Dorado, A.D.; Gamisans, X.; Gabriel, D.
Abstract: Sulfate-reducing bioreactors for sulfide production are the initial stage of processes targeting elemental sulfur recovery from sulfate-rich effluents. In this work, the principal reactions involved in glycerol fermentation and sulfate reduction using glycerol and its fermentation products as electron donors were assessed together with their specific consumption/production rates. A battery of batch activity tests with and without sulfate were performed with glycerol and with each fermentation product using a non-methanogenic but sulfidogenic granular sludge from an up-flow anaerobic sludge blanket (UASB) reactor operated under long-term while fed with crude glycerol. As a result, a mechanistic approach based on the experimental observations is proposed in this work. Glycerol was mainly fermented to 1, 3-propanediol, ethanol, formate, propionate and acetate by fermentative bacteria. All organic intermediates were found to be further used by sulfate reducing bacteria (SRB) for sulfate reduction except for acetate. The most abundant genus detected under sulfidogenic conditions were Propionispora (15.2%), Dysgonomonas (13.2%), Desulfobulbus (11.6%) and Desulfovibrio (10.8%). The last two SRB genera accounted for 22.4% of the total amount of retrieved sequences, which were probably performing an incomplete oxidation of the carbon source in the sulfidogenic UASB reactor. As single substrates, specific sulfate reduction rates (SRRs) using low molecular weight (MW) carbon sources (formate and ethanol) were 39% higher than those using high-MW ones (propionate, 1, 3-propanediol and butanol). However, SRRs in glycerol-fed tests showed that 1, 3-propanediol played a major role in sulfate reduction in addition to formate and ethanol. Graphical abstract: Image 1 Highlights: The mechanisms of sulfate reduction using glycerol were established. Ethanol and 1, 3-propanediol were the main electron donors in sulfate reduction. Incomplete-oxidizing SRB dominated under sulfidogenic conditions. SRB preferentially used simple intermediate products except for acetate.